Influence of feeding systems on the microbial community and flavor characteristics of raw milk: A comparative analysis - Yang Yang; Xiaoyan Wu; Yanwei Xu; Quan Shuang; Ya Nan Xia (Journal of Dairy Science)
ABSTRACT: This study analyzed the composition of the microbial community in raw milk and its effects on flavor compounds by comparing samples from cows raised on pasture (PXN) and in housing (HXN). In August 2023, 9 raw milk samples from Holstein cows were collected from a pasture in the Xilin Gol League, Inner Mongolia, China, and labeled as the PXN group. Simultaneously, 9 raw milk samples were collected from Holstein cows raised by individual farmers in the region and labeled as the HXN group. Metagenomic sequencing technology was used to detect and analyze the dynamics of microbial community in milk samples. At the same time, headspace solid-phase microextraction, electronic nose, and electronic tongue technology were used to monitor the flavor characteristics of raw milk under the 2 feeding conditions and to analyze the correlations between them. The results showed that raw milk protein (PXN, 3.43%; HXN, 3.36%) and fat (PXN, 4.01%; HXN, 3.79%) content in pasture group were higher than that in the housed group, and lactose content (PXN, 4.98%; HXN, 5.12%) and total solid content (PXN, 4.98%; HXN, 5.12%) were lower than that under the housed system. However, there was no significant difference between nonmilk fat solid contents of the 2 groups. The W1C, W5C, W5S, and W2S sensors of the electronic nose played an important role in distinguishing the 2 groups of samples. The sour taste of raw milk in the pasture group was different from that of the in-house feeding group. There were significant differences in the microbial communities of the 2 groups, with Macrococcus caseolyticus (39.85%) in the PXN group and Lactococcus lactis (49.59%) in the HXN group being the dominant bacteria. The volatile compounds of raw milk in the PXN and HXN groups were detected by a headspace solid-phase microextraction method. A total of 62 and 53 flavor compounds were detected in the PXN and HXN groups, respectively. Terpenoids, esters, and aldehydes were dominant in the PXN group, and acids were dominant in the HXN group. The saturated fatty acid content in the HXN group (76.13%) was higher than that in the PXN group (72.47%). The CLA content in the PXN group (3.56 g/100 g) was higher than that in the HXN group (1.32 g/100 g). The dominant strains, that is, Macrococcus caseolyticus, Lactococcus lactis, and Lactococcus cremoris, in both PXN and HXN groups exhibited positive effects on the formation of alcohols, esters, phenols and unsaturated fatty acids. In addition, Macrococcus caseolyticus in the PXN group showed significant positive correlation with calcium lactate. This study comprehensively describes the microbial community structure and flavor quality of raw milk under different feeding methods, which may serve as a reference to control the quality of raw milk.